STANDARDIZATION OF FIELD INOCULATION TECHNIQUES FOR PROGRESSION OF BACTERIAL BLIGHT OF POMEGRANATE IN PUNJAB - ASHISH; ANITA ARORA (The Bioscan, 2015)
Bacterial blight of pomegranate caused by Xanthomonas axonopodis pv. punicae is a wide spread disease affecting its successful production and every year results into 50-100 per cent economic losses depending upon disease severity. Therefore, field experiment was conducted to standardize the field inoculation techniques for progression of bacterial blight. Inoculations were carried out on leaves, twigs, flowers and fruits of Ganesh and Kandhari variety, under field conditions in the month of June, July and August 2013. For inoculations on different plant parts, different methods were used. It was observed that per cent index of bacterial blight was high, when inoculations were carried out in the month of July than in the months of June and August. High disease index was recorded on leaves (73.50 and 71.50 per cent on Ganesh and Kandhari, respectively) and fruit surface (79.50 and 75.50 per cent on Ganesh and Kandhari, respectively). The degree of infection was varied on the inoculated fruit surface (0.161 and 0.143 per unit per day on Ganesh and Kandhari, respectively) and leaves (0.118 and 0.112 per unit per day on Ganesh and Kandhari, respectively), the former showing high level of disease occurrence. Leaf- clip and pinprick method on fruit surface were selected as the suitable inoculation techniques for identifying resistant genotypes of pomegranate against bacterial blight.